An assessment of alcohol consumption using the alcohol use disorders identification test: self-report version questionnaire among students pursuing professional courses - Khan, Huma; Mishra, Saurabh; Pandey, Abhinav; Pandey, Abhinav; ., Abhijeet (International Journal Of Community Medicine And Public Health, 2021)
Background: Harmful use of alcohol is accountable for 7.1% and 2.2% of the global burden of disease for males and females respectively. Alcohol is the leading risk factor for premature mortality and disability among those aged 15 to 49 years, accounting for 10% of all deaths in this age group. Objectives of current study were to assess the prevalence of alcohol consumption students pursuing professional courses and to know the factors associated with alcohol consumption among study participants. Methods: Current study is a cross sectional study with sample size of 410 (male: 49%, female 51%). The alcohol use disorders identification test self-report version by WHO was taken as study tool. Data Collection was done online through Google forms and data analysis was done using SPSS trial version. Results: Mean age of the participants was 21.95±3.03 years. Prevalence of alcohol consumption was found in 17.1% study participants. Conclusions: Alcohol use varies among different academic streams across varied socio demographic backgrounds. Interventions including in campus counselling are need of the hour.